1995
DOI: 10.1111/j.1365-2672.1995.tb03148.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of sodium chloride concentration and pH on the growth of Salmonella typhimurium colonies on solid medium

Abstract: The growth of Salmonella typhimurium colonies on a model food system (agar solidified culture medium) was followed. Colony radius, determined using computer image analysis (IA) techniques, and viable cell number per colony were measured as indices of colony growth, and the effect of [NaCl] (0.5-3.5% (w/v)) and pH (7.0-5.0) on colony growth at 30 degrees C was observed; colonies were point inoculated from serial dilutions. Colony growth (between 13 and 26 h after inoculation) was linear when expressed in terms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 20 publications
1
15
0
Order By: Relevance
“…Katsaras and Leistner (1991) also studied the development of bacteria in fermented sausages. Measurements in or on food model experimental systems have included agar gels (Cooper, Dean, & Hinshelwood, 1968;McKay & Peters, 1995;Mitchell & Wimpenny, 1997;Stecchini, Del Torre, Donda, & Maltini, 2000), gelatin gels (Brocklehurst, Mitchell, & Smith, 1997; and dextran solutions (Hills, Buff, Wright, Sutcliffe, & Ridge, 2001). It has been reported that bacterial growth occurs as discrete colonies in gels and gelled regions of food (Dodd, 1990;Dodd & Waites, 1991;Wimpenny et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Katsaras and Leistner (1991) also studied the development of bacteria in fermented sausages. Measurements in or on food model experimental systems have included agar gels (Cooper, Dean, & Hinshelwood, 1968;McKay & Peters, 1995;Mitchell & Wimpenny, 1997;Stecchini, Del Torre, Donda, & Maltini, 2000), gelatin gels (Brocklehurst, Mitchell, & Smith, 1997; and dextran solutions (Hills, Buff, Wright, Sutcliffe, & Ridge, 2001). It has been reported that bacterial growth occurs as discrete colonies in gels and gelled regions of food (Dodd, 1990;Dodd & Waites, 1991;Wimpenny et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Here, the substances needed for microbial growth such as nutrients and water passed through the membrane from the agar plate to cells. Some investigators inoculated bacterial cells directly on the surface of an agar plate (2,21,24). The membrane filter method has several technical advantages.…”
Section: Resultsmentioning
confidence: 99%
“…The proportionality factor, C s (cell‐surface coefficient), was calculated as described in , and its value for each species was 5·71·10 6 ± 1·48·10 5 for S. cerevisiae , 5·20·10 6 ± 1·25·10 5 for Debaryomyces fabryi , 8·22·10 6 ± 3·85·10 5 for Rhodotorula glutinis and 2·26·10 6 ± 9·44·10 4 for Zygosaccharomyces rouxii , in cells mm −2 . Several types of equations, relating the logarithm of the number of cells and the area or radius of the colony, have been published for bacteria (McKay and Peters ; Harrison et al . ; Guillier et al .…”
Section: Resultsmentioning
confidence: 99%
“…More complex descriptions of the early development of colonies were published, mainly for bacteria (Palumbo et al . ; Reyrolle and Letellier ; Lewis and Wimpenny ; McKay and Peters ; Panikov et al . ; Theys et al .…”
Section: Introductionmentioning
confidence: 99%